STRATEGI PEMBELAJARAN DARING DAN LURING SELAMA PANDEMI COVID-19 PADA MATA PELAJARAN IPA SISWA KELAS VIII SMPN 3 PACAR TAHUN AJARAN 2020/2021 - Agung, Primus; Kaleka, Melkyanus Bili Umbu; Ngapa, Yulius Saprianus Dala (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
This study aims to determine: to describe online and offline learning strategies in science subjects for class VIII at SMPN 3 Pacar. The type of research used is descriptive research with a quantitative approach. The subjects in this study were educators and students of class VIII SMP Negeri 3Pacar, totaling 5 people, science teachers 2 people and also the principal. The object of this research is online and offline learning strategies in science subjects. Data collection instruments in the form of data from interviews, observations and documentation. Data were analyzed descriptively. The results showed that online and offline learning strategies. For offline learning strategies, teachers deliver lessons using strategies such as procurement of material summaries, weekly assignments and home visits. The teacher's online learning strategy uses the WhatsApp application, but it is rarely used because it is constrained by the internet network and also not all students have Android phone.